Falling Through the ‘Savage Slot’: Postcolonial Critique and the Ethnographic Task - Austin-Broos, Diane J. (The Australian journal of anthropology, 1998)
This paper observes that recent theoretical developments in anthropology present a challenge to ethnography understood as a holistic study involved in the task of translation. By addressing the critiques of postcolonial thinkers, and some postmodern thinkers, the paper seeks to re-formulate what the ethnographic task can and should involve at the end of the twentieth century. The discussion is premised on the view that a practice of ethnography is central to a continuing and distinctive identity for anthropology. It is argued, nonetheless, that this can be only an ethnography that has expanded the sites at which it is practised and escaped the classification of the world into ‘the West and the rest’.